PENGARUH PENAMBAHAN CAMPURAN ARANG LIMBAH KULIT PISANG DAN FLY ASH TERHADAP PENURUNAN NILAI RESISTANSI PERTANAHAN ROD GROUNDING - Jagad, Mohammad Wahyu; Dhofir, Moch.; Utomo, Teguh (Jurnal Mahasiswa TEUB, 2024)
One of the efforts that can be made to reduce the value of soil resistance is by providing soil treatment. The most ideal soil treatment is done in the nearest area to the grounding electrode. Soil treatment can be carried out by adding other substances to the soil to engineer soil conditions and reduce the value of soil resistance. This study aims to examine the effect of a mixture of banana peel waste charcoal and fly ash on the reduction of soil resistance values. Banana peel charcoal contains activated carbon that can maintain soil moisture, while fly ash is a residue from coal combustion that contains electrolyte compounds. The homogeneously engineered mixture of banana peel waste charcoal and fly ash has a resistivity of 385.76 Ω-cm. Testing was conducted with three variations of the mixture composition: banana peel charcoal 75% and fly ash 25%, banana peel charcoal 50% and fly ash 50%, and banana peel charcoal 25% and fly ash 75%, with a constant insertion depth of 0.7 meters and a diameter of 0.15 meters. The first mixture successfully reduced soil resistance by 46.1 Ω, or a reduction of 52.77%. The second mixture successfully reduced soil resistance by 40.27 Ω, or a reduction of 46.57%. The third mixture successfully reduced soil resistance by 27.3 Ω, or a reduction of 31.34%. Moisture engineering was carried out by adding 300 ml of water, resulting in a reductionranging from 9.33% to 23.90%. Keywords: Banana peel charcoal, Fly ash, Soil resistance, Soil resistivity, Soil treatment,